Rapid Preparation of Geometrically Optimal Battery Electrode Samples for Nano Scale X-ray Characterisation. Issue 6 (6th April 2020) - Tan, C.; Daemi, S.; Heenan, T.; Iacoviello, F.; Leach, A. S.; Rasha, L.; Jervis, R.; Brett, D. J. L.; Shearing, P. R.
Abstract : Rechargeable lithium-based batteries are one of the key enabling technologies driving the shift to renewable energy, and research into novel technologies has intensified to meet growing demands in applications requiring higher energy and power density. The mechanisms behind battery degradation can be investigated across multiple length-scales with X-ray imaging methods; at the nano-scale severe constraints are imposed on sample size in order to obtain adequate signal to noise. Here, we present a novel laser-milling technique to prepare geometrically optimal samples for X-ray nano-tomography. Advantages of this technique include significantly reduced sample preparation time, and a suitable geometry for mosaic acquisition, enabling a larger field of view to be captured at high spatial resolution, thus improving statistics. The geometry of the resulting electrode remains highly suitable for nano-tomography, and yet permits in situ and operando experiments to be carried out on standard electrode coatings, providing new insights into transient phenomena whilst closely mimicking standard electrochemical cells.